Motivasi Politik Kepala Desa Perempuan Di Provinsi Jawa Timur - Rusta, Andri; Hairunnas, Hairunnas (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
One of the interesting phenomena in the decentralization and regional autonomy process was the emergence of women’s candidates in direct elections of village heads. The village heads are leading public offices in Indonesia local government. Public office, as well as the political office, directly dealing with the public and providing public services to the community. The appearance of women in the political sphere is a new symptom. A women's political role which women tend to put on the condition and position of powerlessness. Women are seen as complementary sufferers in the world of politics, with direct elections the chance to be village heads to be quite strategic and not easy to be achieved for women. However, in the province of East Java, that proved highly viscous Islamic teachings, quite enough women who occupied it. In the last decade, in several villages in East Java province, some women candidates won the election. The political motivation of the women who served as street-level leader is worth a look from the perspective of gender and culture. This article provides a description of the candidate's motivation of women in local elections at village level. As such, research will be able to explain the political motivations of women more comprehensively.Keywords: Women and Politics; Political Motivation; The Women Village Head AbstrakSalah satu fenomena yang menarik dalam proses desentralisasi dan otonomi daerah adalah munculnya kandidat perempuan dalam pemilihan langsung kepala desa. Kepala desa merupakan jabatan publik terdepan dalam local government di Indonesia. Jabatan publik sekaligus jabatan politik yang secara langsung berhadapan dengan publik dan memberikan pelayanan publik kepada masyarakat. Tampilnya perempuan dalam ranah politik ini adalah gejala baru. Peran politik perempuan yang selama ini cenderung menempatkan perempuan pada kondisi dan posisi ketidakberdayaan. Perempuan hanya dipandang sebagai pelengkap penderita dalam dunia politik Dengan pemilihan langsung, peluang untuk menjadi kepala desa menjadi cukup strategis dan tidak gampang untuk diraih bagi perempuan. Akan tetapi, di Provinsi Jawa Timur yang sangat kental ajaran Islamnya ternyata cukup banyak perempuan yang mendudukinya. Dalam sepuluh tahun terakhir, di beberapa desa di Propinsi Jawa Timur beberapa kandidat perempuan berhasil memenangkan pemilihan kepala desa. Motivasi politik perempuan-perempuan yang menjabat sebagai street level leader ini menarik untuk dilihat dari perspektif gender dan kultural. Artikel ini memberikan penjelasan mengenai motivasi kandidat perempuan dalam pemilu lokal di tingkat desa. Dengan demikian penelitian akan mampu menjelaskan secara lebih komprehensif tentang motivasi politik perempuan.Kata Kunci:Perempuan dan Politik; Motivasi Politik; Kepala Desa Perempuan